Determinants of scabies outbreak in Takusa district of Amhara Region, Northwest Ethiopia - Etsehiwot D. Worku; Mulusew A. Asemahagn; Melese L. Endalifer (AOSIS, 2020)
Background: Human scabies is a highly contagious human dermatitis disease. As indicated by the national and regional reports, the epidemic of scabies became a major public health problem in Ethiopia since 2015. Objective: To identify the determinant factors of scabies outbreak in Takusa district, Northwest Ethiopia, 2017. Methods: A community based unmatched case-control study among 188 participants (63 cases and 125 controls) was conducted in Takusa district from September to October 2017. Data were collected using a pretested structured questionnaire. Multivariable logistic regression analysis was computed using SPSS version 22 to identify factors associated with scabies. Odds ratio at 95% CI and p-value less than 0.05 were used to describe the strength of the association and statistical significance. Results: The median age of cases was 20 years (ranges1-61). Presence of person with itching in the family (AOR=7.7, 95% CI:1.9-30.5), sleeping with scabies patient (AOR=3.99, 95% CI:1.37-11.7), travel to scabies epidemic area in the last six weeks (AOR=3.79, 95%CI:1.28-11.1) and infrequent use of detergent for showering (AOR=4.85; 95% CI: 1.3-17.9)) were found to be determinant factors of scabies outbreak. Conclusion: Frequent contact with people who develop scabies at home, not using detergents for washing, and mobility of people from non-epidemic to the epidemic areas were determinant factors. Giving special emphasis on regular awareness creation to the rural community is important to prevent scabies outbreak.